2014
DOI: 10.1007/s13142-013-0242-z
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal loss and program fidelity: impact of the economic downturn on HIV/STI prevention program fidelity

Abstract: The economic downturn of 2007 created significant fiscal losses for public and private agencies conducting behavioral prevention. Such macro-economic changes may influence program implementation and sustainability. We examined how public and private agencies conducting RESPECT, a brief HIV/STI (sexually transmitted infection) counseling and testing intervention, adapted to fiscal loss and how these adaptations impacted program fidelity. We collected qualitative and quantitative data in a national sample of 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…We used published statistics from the original RESPECT randomized-control trial [ 25 , 26 ] and CDC publications characterizing standard program structure and protocols [ 28 ] to inform overall model design. We also used data from two RESPECT implementation studies to inform the characterization of human resources and acquire data on RESPECT clients, staff, and agencies [ 29 32 ]. Specific variables, descriptions, values, and empirical data sources for each variable used to inform simulation runs are provided in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…We used published statistics from the original RESPECT randomized-control trial [ 25 , 26 ] and CDC publications characterizing standard program structure and protocols [ 28 ] to inform overall model design. We also used data from two RESPECT implementation studies to inform the characterization of human resources and acquire data on RESPECT clients, staff, and agencies [ 29 32 ]. Specific variables, descriptions, values, and empirical data sources for each variable used to inform simulation runs are provided in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Although the present study does not directly assess program fidelity, our findings do suggest that there may be challenges with the OraQuick training component that may pose difficulties for some consumers in attainting high implementation fidelity. Program fidelity [42] here means that consumers will perform all procedures and recommendations competently enough to • "faint line could be confusing-bring more attention to the faint line in the instructions" • "Youth don't understand-they may not understand that there's a chance the test could be wrong. They may trust the test so much that they don't seek confirmatory care."…”
Section: Overviewmentioning
confidence: 99%
“…Program fit is consistently identified as important to successful program implementation [47] and represents a potential point of intervention in efforts to increase program fidelity. Although a number of HIV prevention studies have shown that poor program-client fit by agencyimplemented programs results in low program fidelity [42,[48][49][50][51][52][53], none of this work has examined selfimplemented programs.…”
Section: Overviewmentioning
confidence: 99%
“…Although we constructed a purposive sample of agencies from all regions of the USA, data are based on convenience samples of agencies and of clients, and findings may not generalize. Our measure of fidelity also has limitations [also see 37]. We were unable to assess counseling strategies that clients may not recognize (e.g., teachable moment), nor did we assess quality of delivery (i.e., competence fidelity).…”
Section: Limitationsmentioning
confidence: 99%